Multiple Honey Harvesting Strategy - migratory Beekeeping in Tamil Nadu and Puducherry, India - Nishanthini , K.; Kanagarajan , R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Commercial beekeeping in Tamil Nadu and Puducherry depends on Indian bee, Apis cerana indica. The State had occupied first position in honey production in the country until 1990’s. In commercial beekeeping, migration has assumed really important dimensions. Our results demonstrated that total brood area reached the highest area of 1286.86 cm2 at January II at Puducherry site and lowest brood area at May II (527.38 cm2) at Chidambaram sites. Similarly, a significant difference was noticed in the mean total brood area, pollen area and queen prolificacy between the different migratory sites. Pollen area (cm2) was 155.22±7.88 to 272.56±9.61 cm2. The largest fortnightly mean pollen area was in February I (272.56±9.61 cm2) at Puducherry site, while the lowest was in June II (165.46±7.30 cm2) Chidambaram site. Egg laying area peaked in January II (297.81±4.75 cm2) at Puducherry site and rapidly declining through February, March, and April to reach its lowest point in May II (122.05±4.26 cm2) at Chidambaram site. In contrast, a non-significant difference was observed in nectar area and honey yield at different migratory sites (P>0.05). Current findings add to our understanding the honey yield was high in all the migratory sites without any differences by the way multiple honey harvest was possible in migratory beekeeping practices.